Digit ratio (2D:4D) and physical fitness (Eurofit test battery) in school children. Issue 5 (May 2015) - Ranson, R.; Stratton, G.; Taylor, S.R.
Abstract Background The relative lengths of the index finger to the ring finger (2D:4D) is sexually dimorphic and is thought to be a correlate of prenatal sex steroids (low 2D:4D = high prenatal testosterone and low prenatal oestrogen). In adults there have been reports that low 2D:4D is consistently associated with high sports performance. Aims To investigate correlations between 2D:4D and fitness levels in children. Study design Right 2D:4D and body size were measured, in addition to flexibility, speed, endurance and strength (Eurofit tests). Subjects: 922 boys and 835 girls (mean ages (years): 10.8 ± 1.01 and 10.07 ± 1.00 respectively). Outcome measures: height, mass, BMI, triceps and subscapular skinfolds, 20 m shuttle run, sit and reach, standing broad jump, hand grip strength, 10 × 5 m sprint, and the sit and reach test. Results Boys significantly outperformed the girls in the 10 × 5 m sprints, the 20 m shuttle run, standing broad jump, and hand grip strength. In boys but not girls, 2D:4D was significantly negatively correlated with scores in all these tests except the standing broad jump. In girls but not boys, 2D:4D was significantly positively correlated to stature, mass, BMI and waist circumference. Conclusions It is suggested that high prenatal testosterone and low prenatal oestrogen (low 2D:4D) is implicated in high sprinting speed, endurance and hand grip strength in boys. In girls low prenatal testosterone and high prenatal oestrogen is associated with large body size.